Indications for β‐Blocker Prescriptions in Heart Failure with Preserved Ejection Fraction. Issue 7 (16th May 2019) - Yum, Brian; Archambault, Alexi; Levitan, Emily B.; Dharamdasani, Tina; Kneifati‐Hayek, Jerard; Hanlon, Joseph T.; Diaz, Ivan; Maurer, Mathew S.; Lachs, Mark S.; Safford, Monika M.; Goyal, Parag
Abstract : OBJECTIVES: To better understand indications for β‐blocker (BB) prescriptions among older adults hospitalized with heart failure with preserved ejection fraction (HFpEF). DESIGN/SETTING: Retrospective observational study of hospitalizations derived from the geographically diverse Reasons for Geographic and Racial Differences in Stroke cohort. PARTICIPANTS: We examined Medicare beneficiaries aged 65 years or older with an expert‐adjudicated hospitalization for HFpEF (left ventricular ejection fraction = 50% or greater). MEASUREMENTS: Discharge medications and indications for BBs were abstracted from medical records. RESULTS: Of 306 hospitalizations for HFpEF, BBs were prescribed at discharge in 68%. Among hospitalizations resulting in BB prescriptions, 60% had a compelling indication for BB—44% had arrhythmias, and 29% had myocardial infarction (MI) history. Among the 40% with neither indication, 57% had coronary artery disease (CAD) without MI and 38% had hypertension alone (without arrhythmia, MI, or CAD), both clinical scenarios with little supportive evidence of benefit of BBs. Among hospitalizations resulting in BB prescription at discharge, 69% had geriatric conditions (functional limitation, cognitive impairment, hypoalbuminemia, or history of falls). There were no significant differences in the prevalence of geriatric conditions between hospitalizations of individuals with compelling indications for BBs and hospitalizations of individuals with noncompelling indications. CONCLUSIONS: BBs are commonly prescribed following a hospitalization for HFpEF, even in the absence of compelling indications. This occurs even for hospitalizations of individuals with geriatric conditions, a subpopulation who may be at elevated risk for experiencing harm from BBs.